Smartphone screen time reduction improves mental health: a randomized controlled trial - Pieh, Christoph; Humer, Elke; Hoenigl, Andreas; Schwab, Julia; Mayerhofer, Doris; Dale, Rachel; Haider, Katja (BMC medicine, 2025)
Background Smartphone screen time has risen sharply in recent years. Even though an association between smartphone use and mental health is well documented, it is still unclear whether this is simply a correlation or causality. The aim of this study is to investigate the effects of smartphone screen time reduction on mental health indicators. Methods This non-blinded, parallel randomized controlled trial (RCT) was performed to investigate the impact of a 3-week screen time reduction to ≤ 2 h/d in healthy students on stress (PSQ), well-being (WHO-5), depressive symptoms (PHQ-9), and sleep quality (ISI) at baseline (t0), post-intervention (t1), and at follow-up (t2 = 6 weeks after t1). For the intention to treat analysis, repeated measures ANOVAs and post-hoc tests (for time as well as group differences) were performed and effect sizes were presented as partial eta squared (η 2 = time × group) and group-mean differences. Results In total, 111 out of 125 healthy students (70 females; mean age = 22.68 ± 2.6 years; mean screen time = 276 ± 115.1 min/day) were randomly assigned to intervention—( n = 58; 3 weeks of screen time reduction to ≤ 2 h/day) or control group ( n = 53). Although no differences were observed at baseline (t0), significant post-intervention (t1) effects of small to medium size were observed on well-being (η 2 = .053), depressive symptoms (η 2 = .109), sleep quality (η 2 = .048), and stress (η 2 = .085). Significant group differences ( p ≤ .05) were found post-intervention (t1) for depressive symptoms ( Mean Difference ( MD) = 2.11, Standard Error ( SE) = 0.63, 95% Confidence Interval (CI) [0.87, 3.36]), sleep quality ( MD = 2.59, SE = 0.97, 95% CI [0.66, 4.51]), well-being ( MD = -1.54, SE = 0.68, 95% CI [.-2.89, -0.18]), and stress ( MD = 6.91, SE = 3.48, 95% CI [0.01, 13.81]). Screen time increased rapidly after the intervention and at follow-up the values were once again approaching the initial level. Conclusions The study highlights mental health improvements through smartphone screen time reduction. Three weeks of screen time reduction showed small to medium effect sizes on depressive symptoms, stress, sleep quality, and well-being. The results suggest a causal relationship, rather than a merely correlative one, between daily smartphone screen time and mental health. Trial registration The study was preregistered on Open Science Framework (trial registration number: A9K76) on November 8, 2023.